Transformasi Hermeneutika: Perkembangan dari Tradisi Penafsiran Klasik Menuju Hermeneutika Filosofis - Rian R; Barsihannor B; Muhaemin Latif (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Understanding is nothing but a characteristic of humans themselves, some even say it is the way humans exist. In the realm of history, it turns out that understanding or hermeneutics continues to develop, until it bears fruit in understanding maturity. This article attempts to explore the development of hermeneutics from the classical era to the modern saman. By using the descriptive-analytical method, it is concluded that the fundamental difference between hermeneutics between classical and modern times is their escape from the confines of the church. Classical hermeneutics is used solely to interpret the Bible, while modern hermeneutics is used to seek meaning not only in sacred texts but also in profane texts. At a more philosophical level, hermeneutics is understood as an attempt to understand understanding. This effort led to the conclusion that all understanding cannot be separated from the element of subjectivity.